Neutrales Rufnamengenus zwischen Grammatik und Pragmatik - Busley, Simone; Fritzinger, Julia (Linguistik Online, 2021)
In numerous German dialects and in Luxembourgish, female first names can take on both feminine and neuter gender agreement, thus leading to gender variation on a paradigmatical level and gender mismatches on a syntactical level. This is contradictory to canonical conceptions of gender systems and can be interpreted as a case of degrammaticalization. Here, grammatical gender has been refunctionalized as a socio-pragmatic marker which indicates the age and status of the woman referred to as well as the speaker’s relationship to her. In some varieties, regrammaticalization of gender assignment resulted in female first names always taking neuter agreements. The present article focusses on the reconstruction of the stages of degrammaticalization and regrammaticalization of gender assignment based on data of the research project “Das Anna und ihr Hund – Weibliche Rufnamen im Neutrum”. Analyses of the data indicate that personal pronouns as the targets most prone to differing agreement played a key role in this process.